Utilization of NaCl Solution of Moringa Oleifera Seed Extract as Natural Coagulant at Liquid Waste at PT. Cheil Jedang Indonesia – Jombang - Rizqi, Wadziatir; Yulianti, Eny; Jannah, Akyunul (ALCHEMY, 2015)
In this study, the coagulant from Moringa seeds extracted using NaCl solution. Early stages, Moringa seed powder was extracted using 1M NaCl solution. Variations in sample pH (pH 4, 5, 6, 7, 8, 9 and 10) and variations in coagulant dose (10, 20, 30, 40, 50, 60, 70 and 80 mL / L) was conducted to determine the effectiveness of each coagulant at pH test parameters, Total Suspended Solids and Chemical Oxygen Demand-Permanganate method. Characterization of Moringa seed extract solutions include levels of carbohydrates, proteins, fats and amino acids. Characterization results, the carbohydrate content of Moringa seeds extracted with NaCl solution at 909 ppm, the protein 3348 ppm, fat content 800 ppm and it contains 14 kinds of amino acids. Concentration of most amino acids are lysine, which is 0.196%. Coagulant of Moringa seed extract solution of NaCl with an optimum pH of 10 can decreased levels of TSS by 82.3% at a dose of 80 mL / L. Coagulant solution of NaCl extract of Moringa seeds can not reduce levels of COD-Mn.Keywords: Chemical Oxygen Demand-Permanganate, Coagulant, Moringa oleifera, Total Suspended Solids